Analysis of ENO scheme slope limiters (Journal of Mathematics Mechanics and Computer Science, 2014)
The interaction of the three-dimensional supersonic turbulent air fl ow with the transversely injected hydrogen jet is numerically simulated by solving the Reynold s-averaged NavierStokes equations using the ENO (essentially non-oscillatory) scheme of the third order of accuracy. Since the choice of the limiter functions significantly a ffects the accuracy of the problem, preliminary test problems are solved to validate numerical method and choose optimal slope limiter. Analysis of the different variati ons of the limiter functions for developed algorithm was done to define optimal function produced the smallest solution spreading. Then, the effect of the different variations of the limiter functions for developed algorithm on the mixing layer is studied since the exact calculation of the mass concentration spreading is important issue in combustion pr oblem modeling. Also, by numerical experiments the effect of the slope limiters on the shock-wave structure formation is studied. It was shown that choice of some limiters can result in excessive expansion of the mixing layer, that is important issue in numeri cal modeling of scramjet engine. As result, the optimal limiter function which produces the sm allest spread of solution for the spatial problem was defined. Also the mechanism o f the formation of vortices in front of the injected jet and behind that is studied.
Keywords: supersonic flow; multicomponent gas; ENO scheme; limiters; Navier- Stokes equations.